School Culture-Based Character Education: Implementation of Strengthening Religious Character in Islamic Primary Schools - Cahyanto, Bagus (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2023)
Character is an important part to be developed in educational practices at school. Elementary schools as the foundation for instilling values ​​have a strategic role in strengthening the character of students. This research aims to reveal the practice of strengthening religious character based on school culture at MI Al Ma'arif 07 Singosari Malang. Researchers used a descriptive qualitative approach, where data collection was carried out through interviews, observation and documentation. Researchers used a descriptive qualitative approach in this research, where data collection was carried out through various methods to gain an in-depth understanding of the phenomenon under study. This approach was chosen to dig deeper into the processes and experiences experienced by the research subjects, as well as the context in which the school culture-based religious character strengthening program was implemented. Based on the research results, it shows that all elements in the school are able to collaborate well to create a strong religious character in students. Various religious programs are designed and implemented regularly to achieve this goal. Schools understand the importance of forming students' religious character from an early age as a foundation for future life. The findings in this research are that the practice of strengthening religious character based on school culture is carried out through various programs including congregational Dhuha prayers, congregational Dhuhur prayers, reciting Juz Ama before learning, reading surah yaasiin and tahlil on Fridays, reciting Rotibul Hadad, and literacy activities.